Some Quality Traits of White Sweet Clover Collected from Natural Flora - Erdem Gülümser; Hanife Mut; Medine Çopur Doğrusöz; Uğur Başaran (Turkish Journal of Agriculture: Food Science and Technology)
In turkey, one of the most important problem of livestock’s production is insufficiency of quality forage crop, but still few forage species are cultivated. On the other hand, conservation of plant genetic resources has become an important problem in the world today. Indeed, biodiversity is an indispensable element of human life, especially food, and it is estimated that 20% of these resources will extinct by 2030. The aim of study was to determine some quality traits of white sweet clover (Melilotus alba Desr.) collected from natural flora of Bilecik province. In this study, plants were collected at the flowering stage and investigated of 17 genotypes. The determined quality traits of genotypes as fallows; crude protein, ADF, NDF, RFV, K, P, Mg, Ca and Ca/P, and these traits were noted as11.99-21.07%, 27.70-40.53%, 43.31-55.84%, 93.44-147.02, 1.300-2.807%, 0.187-0.310%, 0.127-0.350%, 0.490-1.417% and 2.05-5.92%, respectively. As a result of the study, it has been determined that the quality of the white sweet clover genotypes collected from Bilecik natural flora have been sufficient for animal feeding and have a significant potential for future breeding activities.